Modified single-crystal high-nickel ternary positive electrode material, preparation method and application thereof

CN121627075BActive Publication Date: 2026-10-30YIBIN LIBODE NEW MATERIAL CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202511829048.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-12-05
Publication Date
2026-10-30
Estimated Expiration
2045-12-05

AI Technical Summary

Technical Problem

[0004]本发明的目的在于提供一种改性单晶高镍三元正极材料及其制备方法与应用,以解决或改善上述技术问题

Benefits of technology

本发明提供的方法能够使改性单晶高镍三元正极材料具有更多的活性晶面(104),有利于提高离子传输效率;包覆的Li3PO4和非晶态Li3BO3复合离子导体可作为缓冲和过渡层,有效隔绝单晶颗粒表面与硫化物电解质之间直接接触,抑制正极与硫化物电解质之间的界面副反应,不仅可以提高正极的结构稳定性,还提高离子电导率,改善了硫化物全固态电池的电化学性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121627075B_ABST
    Figure CN121627075B_ABST
Patent Text Reader

Abstract

The application discloses a modified single-crystal high-nickel ternary positive electrode material and a preparation method and application thereof, and belongs to the technical field of battery materials. The method comprises the following steps: mixing a ternary positive electrode material precursor, a lithium source, a molybdenum source and a barium source, and then performing sintering to obtain a single-crystal ternary positive electrode material with a (104) crystal surface as a leading one and a cubic structure; and mixing the single-crystal ternary positive electrode material with Li3PO4 and Li3BO3, and then performing calcination to obtain the modified single-crystal high-nickel ternary positive electrode material. The method can make the modified single-crystal high-nickel ternary positive electrode material have more active crystal surfaces (104), and effectively improve ion transmission efficiency; the coated Li3PO4 and amorphous Li3BO3 composite ion conductors can be used as buffer and transition layers, effectively isolate direct contact between the single-crystal particle surface and a sulfide electrolyte, not only improve ion conductivity, but also effectively prevent interface side reactions, and improve the electrochemical performance of a sulfide full solid-state battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of battery materials technology, and more specifically, to a modified single-crystal high-nickel ternary cathode material, its preparation method, and its application. Background Technology

[0002] All-solid-state batteries have attracted much attention due to their non-flammable, high-temperature resistant, and non-volatile solid electrolytes, and are considered one of the most promising next-generation energy storage devices. Among all-solid-state batteries, sulfide solid electrolytes are particularly noteworthy for their high ionic conductivity (10⁻⁶ Ω·cm). -3 S / cm~10 -2 The S / cm ratio has become a research hotspot. However, the interfacial compatibility between sulfide solid electrolytes and existing mainstream layered lithium-ion battery cathode materials is poor, with a severe space charge layer effect, resulting in high ionic resistance at the interface between the cathode material and the sulfide solid electrolyte, thus limiting the migration of lithium ions between the two materials. In addition, ternary cathode materials are prone to side reactions with sulfide solid electrolytes under high voltage conditions, affecting the electrochemical performance of sulfide all-solid-state batteries.

[0003] In view of this, the present invention is proposed. Summary of the Invention

[0004] The purpose of this invention is to provide a modified single-crystal high-nickel ternary cathode material, its preparation method and application, in order to solve or improve the above-mentioned technical problems.

[0005] This invention can be implemented as follows: In a first aspect, the present invention provides a method for preparing a modified single-crystal high-nickel ternary cathode material, comprising the following steps: mixing a ternary cathode material precursor, a lithium source, a molybdenum source and a barium source and then sintering them to obtain a single-crystal ternary cathode material with (104) crystal plane as the dominant crystal plane and a cubic structure. The single-crystal ternary cathode material was mixed with Li3PO4 and Li3BO3 and then calcined to obtain a modified single-crystal high-nickel ternary cathode material with surface-coated Li3PO4 and amorphous Li3BO3 composite ionic conductor.

[0006] In an optional embodiment, the ratio of the total molar amount of Ni, Co, and Mn in the ternary cathode material precursor to the molar amount of Li in the lithium source is 1:(1.04~1.08); the doping amount of Mo in the molybdenum source is 2000ppm~10000ppm, and the doping amount of Ba in the barium source is 1000ppm~5000ppm.

[0007] In an optional implementation, the molecular formula of the ternary cathode material precursor is Ni. x Co y Mn z(OH)₂, of which 0.8 <x<0.96,0<y<0.1,0<z<0.1,x+y+z=1; And / or, the lithium source includes lithium hydroxide; And / or, the molybdenum source includes molybdenum oxide; And / or, the barium source includes at least one of barium hydroxide, barium chloride, barium nitrate, and barium carbonate.

[0008] In an optional embodiment, sintering includes a first stage of sintering, a second stage of sintering, a third stage of sintering, and a fourth stage of sintering; The sintering process is as follows: the first sintering temperature is 450℃~560℃ and the time is 2h~4h; the second sintering temperature is 700℃~800℃ and the time is 3h~6h; the third sintering temperature is 880℃~1000℃ and the time is 1h~5h; and the fourth sintering temperature is 700℃~800℃ and the time is 2h~5h.

[0009] In an optional implementation, the entire sintering process is carried out in an oxygen atmosphere.

[0010] In an optional embodiment, the mass of Li3PO4 and Li3BO3 coated on the surface of the single-crystal ternary cathode material is independently 2000ppm to 10000ppm.

[0011] In an optional embodiment, the calcination temperature is 300℃~500℃ and the calcination time is 8h~12h.

[0012] Secondly, the present invention provides a modified single-crystal high-nickel ternary cathode material, which is prepared by any of the preparation methods described in the foregoing embodiments.

[0013] Thirdly, the present invention provides a positive electrode sheet, wherein the active material of the positive electrode sheet is the single-crystal high-nickel ternary positive electrode material of the aforementioned embodiments.

[0014] Fourthly, the present invention provides an all-solid-state battery containing the positive electrode sheet of the aforementioned embodiments.

[0015] The beneficial effects of this invention include: The method provided by this invention enables modified single-crystal high-nickel ternary cathode materials to have more active crystal faces (104), which is beneficial to improving ion transport efficiency. The coated Li3PO4 and amorphous Li3BO3 composite ion conductor can serve as a buffer and transition layer, effectively isolating the direct contact between the surface of the single crystal particles and the sulfide electrolyte, suppressing the interfacial side reactions between the cathode and the sulfide electrolyte, which can not only improve the structural stability of the cathode, but also improve the ionic conductivity and improve the electrochemical performance of the sulfide all-solid-state battery. Attached Figure Description

[0016] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation on the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.

[0017] Figure 1 The image shows a SEM image of the modified single-crystal high-nickel ternary cathode material prepared in Example 1.

[0018] Figure 2 The image shows the XRD pattern of the modified single-crystal high-nickel ternary cathode material prepared in Example 1. Detailed Implementation

[0019] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased commercially.

[0020] The modified single-crystal high-nickel ternary cathode material provided by this invention, its preparation method, and its application are described in detail below.

[0021] This invention provides a method for preparing a modified single-crystal high-nickel ternary cathode material, comprising the following steps: S1: The ternary cathode material precursor, lithium source, molybdenum source and barium source are mixed and sintered to obtain a single crystal ternary cathode material dominated by the (104) crystal plane.

[0022] By introducing molybdenum and barium sources, the grain growth kinetics can be controlled, promoting the formation of more (104) crystal faces. In addition, if only a molybdenum source is used, more molybdenum source doping is required to form more (104) crystal faces. However, excessive molybdenum source doping will limit crystal growth kinetics and inhibit crystal growth. Therefore, this invention, by combining molybdenum and barium sources, can expose more (104) crystal faces without affecting grain growth.

[0023] In some optional embodiments, the ratio of the total molar amount of Ni, Co, and Mn in the ternary cathode material precursor to the molar amount of Li in the lithium source is 1:(1.04~1.08); the doping amount of Mo in the molybdenum source is 2000ppm~10000ppm, and the doping amount of Ba in the barium source is 1000ppm~5000ppm.

[0024] That is, the total molar amount of Ni, Co and Mn in the ternary cathode material precursor and the molar amount of Li in lithium hydroxide can be 1:1.04, 1:1.05, 1:1.06, 1:1.07 or 1:1.08, or other values ​​in the range of 1:(1.04~1.08).

[0025] The Mo doping concentration of the molybdenum source can be 2000ppm, 3000ppm, 4000ppm, 5000ppm, 6000ppm, 7000ppm, 8000ppm, 9000ppm or 10000ppm, or other values ​​in the range of 2000ppm to 10000ppm.

[0026] The Ba doping amount of the barium source can be 1000ppm, 2000ppm, 3000ppm, 4000ppm or 5000ppm, or other values ​​in the range of 1000ppm to 5000ppm.

[0027] If the amount of Ba doping is too small, it is not conducive to the formation of a single crystal material dominated by the (104) crystal plane; if the amount of Ba doping is too large, it is easy to reduce the material capacity, rate capability and other properties.

[0028] In some optional embodiments, the molecular formula of the above-mentioned ternary cathode material precursor is Ni. x Co y Mn z (OH)₂, of which 0.8 <x<0.96,0<y<0.1,0<z<0.1,x+y+z=1。

[0029] The lithium source mentioned above may include lithium hydroxide.

[0030] The molybdenum source mentioned above may include molybdenum oxide.

[0031] The barium source may include at least one of barium hydroxide, barium chloride, barium nitrate, and barium carbonate.

[0032] In some alternative implementations, sintering includes a first stage sintering, a second stage sintering, a third stage sintering, and a fourth stage sintering.

[0033] The sintering temperature for the first stage can be between 450℃ and 560℃, such as 450℃, 500℃, 520℃, 540℃, or 560℃, or other values ​​within the range of 450℃ to 560℃. The sintering time for the first stage can be between 2h and 4h, such as 2h, 2.5h, 3h, 3.5h, or 4h, or other values ​​within the range of 2h to 4h.

[0034] This sintering stage mainly serves as a pre-sintering process to melt the lithium source and achieve uniform contact between materials, thereby ensuring a sufficient and uniform lithiation reaction during subsequent sintering.

[0035] The sintering temperature for the second stage can be 700℃~800℃, such as 700℃, 720℃, 750℃, 780℃, or 800℃, or other values ​​within the range of 700℃~800℃. The sintering time for the second stage can be 3h~6h, such as 3h, 4h, 5h, or 6h, or other values ​​within the range of 3h~6h.

[0036] The primary function of this second-stage sintering is to regulate the formation of a layered phase structure in the material, thereby preventing the formation of rock salt phase grains. If the temperature of the second-stage sintering is below 700℃, it is detrimental to the formation of a layered phase structure; if the temperature is above 800℃, it will lead to the formation of more material defects. If the second-stage sintering time is less than 3 hours, it is not conducive to the full formation of a layered phase structure; if the second-stage sintering time is longer than 6 hours, it is detrimental to the material's performance.

[0037] The sintering temperature for the third stage can be between 880℃ and 1000℃, such as 880℃, 900℃, 920℃, 950℃, or 1000℃, or other values ​​within the range of 880℃ to 1000℃. The sintering time for the third stage can be between 1 hour and 5 hours, such as 1 hour, 2 hours, 3 hours, 4 hours, or 5 hours, or other values ​​within the range of 1 hour to 5 hours.

[0038] The sintering process in this third stage primarily serves to promote grain growth. If the sintering temperature in the third stage is below 880℃, it is detrimental to grain growth; if the temperature is above 1000℃, it will result in excessively large grain sizes. Similarly, if the sintering time in the third stage is less than 1 hour, it is also detrimental to grain growth; if the sintering time is more than 5 hours, it will lead to excessively large grain sizes.

[0039] The sintering temperature for the fourth stage can be between 700℃ and 800℃, such as 700℃, 720℃, 750℃, 780℃, or 800℃, or other values ​​within the range of 700℃ to 800℃. The sintering time for the fourth stage can be between 2h and 5h, such as 2h, 3h, 4h, or 5h, or other values ​​within the range of 2h to 5h.

[0040] The sintering in this section mainly serves as an annealing process, making the structure formed after the third sintering section more stable and with fewer defects.

[0041] The sintering of each of the above sections is carried out in an oxygen atmosphere, and the heating rate can be set to 2℃ / min~6℃ / min.

[0042] After the fourth sintering stage is completed, the product is allowed to cool naturally to room temperature. Then, the sintered product is subjected to jaw crusher, roller crusher, airflow crusher, and sieve.

[0043] As mentioned above, the morphology of conventional single-crystal high-nickel ternary cathode materials is currently randomly distributed. Due to the different lithium-ion diffusion capabilities of different crystal facets, the ionic conductivity of the system is low after the single-crystal particles come into contact with the solid electrolyte, which limits the migration of lithium ions between the two materials. In addition, the oxygen release capabilities corresponding to different crystal facets in single-crystal ternary cathode materials are also different. The active oxygen ions released from the surface of cathode materials with poor structural stability under high charge state will undergo exothermic-gas-generating behavior with sulfide electrolytes, affecting the electrochemical performance and safety of sulfide all-solid-state batteries.

[0044] This invention prepares a single-crystal ternary cathode material dominated by the (104) crystal plane by co-doping with Mo and Ba elements. This single-crystal ternary cathode material reduces the (003) inactive crystal plane and exposes more active crystal planes (104) which are conducive to lithium-ion transport, thereby improving lithium-ion transport efficiency and improving the rate performance of the material.

[0045] Furthermore, the lattice oxygen ion stability was improved by using Mo and Ba elements for co-doping of single crystals. The lattice oxygen ion stability of the (104) crystal plane is generally better than that of the (003) crystal plane. Increasing the (104) crystal plane can improve the thermal stability of single-crystal ternary cathode materials, effectively suppress the harmful exothermic-gas-generating behavior of active oxygen ions released from the surface of ternary cathode materials under high charge state with sulfide electrolyte, thereby improving the safety of sulfide all-solid-state batteries.

[0046] S2: The single-crystal ternary cathode material is mixed with Li3PO4 and Li3BO3 and then calcined to obtain a modified single-crystal high-nickel ternary cathode material with surface-coated Li3PO4 and amorphous Li3BO3 composite ionic conductor.

[0047] In some alternative implementations, the mass of Li3PO4 and Li3BO3 coated on the surface of the single-crystal ternary cathode material can independently be 2000ppm to 10000ppm.

[0048] That is, the mass of Li3PO4 coated on the surface of the single-crystal ternary cathode material can be 2000ppm, 5000ppm, 8000ppm or 10000ppm, or other values ​​in the range of 2000ppm to 10000ppm.

[0049] The mass of Li3BO3 coated on the surface of the single-crystal ternary cathode material can be 2000ppm, 5000ppm, 8000ppm or 10000ppm, or other values ​​in the range of 2000ppm to 10000ppm.

[0050] In this invention, the method of simultaneously coating Li3PO4 and Li3BO3 by mixing them together achieves a better coating effect than coating only Li3PO4 or Li3BO3, or coating Li3PO4 and Li3BO3 in two separate steps in sequence. This method is more conducive to lithium-ion transport and better suppresses interfacial side reactions.

[0051] In some alternative embodiments, the calcination temperature can be 300℃~500℃, such as 300℃, 350℃, 400℃, 450℃ or 500℃, or other values ​​within the range of 300℃~500℃.

[0052] The calcination time can be 8h to 12h, such as 8h, 9h, 10h, 11h or 12h, or other values ​​within the range of 8h to 12h.

[0053] It should be noted that current methods for surface coating modification of cathode materials only result in coatings adhering to the material surface, lacking good ionic conductivity and failing to effectively improve the electrochemical and rate performance of the material. Furthermore, existing sulfide-based all-solid-state lithium battery cathode materials are prone to side reactions with the electrolyte under high voltage conditions, affecting the battery's electrochemical performance.

[0054] This invention utilizes a composite ionic conductor, Li3PO4 and amorphous Li3BO3, coated onto a cubic single crystal with a (104) crystal plane as its dominant crystal surface. This composite ionic conductor acts as a buffer and transition layer, effectively isolating the single crystal particle surface from direct contact with the sulfide electrolyte and significantly reducing interfacial impedance. The coating of Li3PO4 and Li3BO3 not only improves lithium-ion conductivity but also effectively prevents severe interfacial side reactions, thereby improving the electrochemical performance of the battery.

[0055] Accordingly, the present invention also provides a modified single-crystal high-nickel ternary cathode material, which is prepared by the above-described preparation method.

[0056] The modified single-crystal high-nickel ternary cathode material is dominated by the (104) crystal plane and has a cubic structure. It is doped with both Mo and Ba, and its surface is coated with Li3PO4 and Li3BO3.

[0057] In addition, the present invention also provides a positive electrode sheet, wherein the active material of the positive electrode sheet is the above-mentioned single-crystal high-nickel ternary positive electrode material.

[0058] Furthermore, the present invention also provides an all-solid-state battery containing the aforementioned positive electrode. This all-solid-state battery exhibits good electrochemical performance.

[0059] The features and performance of the present invention will be further described in detail below with reference to embodiments.

[0060] Example 1 This embodiment provides a modified single-crystal high-nickel ternary cathode material, the preparation method of which includes: S1: Ni, a precursor for ternary cathode materials 0.9 Co 0.05 Mn 0.05 (OH)2 and lithium hydroxide are mixed evenly in a high-speed mixer with a molar ratio of (Ni+Co+Mn):Li of 1:1.06, a molybdenum oxide doping amount of 3000ppm, and a barium hydroxide doping amount of 2000ppm. The mixture is then loaded into a sagger and sintered in a high-temperature atmosphere box furnace.

[0061] The sintering process included four stages: a first stage, a second stage, a third stage, and a fourth stage. The sintering atmosphere was oxygen, and the heating rate during the sintering process was 3℃ / min. Specifically, the temperature of the first stage sintering was 500℃ for 3 hours; the temperature of the second stage sintering was 780℃ for 5 hours; the temperature of the third stage sintering was 950℃ for 2 hours; and the temperature of the fourth stage sintering was 780℃ for 4 hours. After sintering, the material was allowed to cool naturally to room temperature to obtain the sintered product. The sintered product was then subjected to jaw crusher, roller crusher, airflow milling, and sieve pulverization to obtain a cubic ternary cathode material with a (104) crystal plane as the dominant morphology.

[0062] S2: The above-mentioned single-crystal ternary cathode material is mixed with Li3PO4 with a coating amount of 5000ppm and Li3BO3 with a coating amount of 2000ppm. The mixture is mechanically mixed for 1.5h. The mechanically mixed mixture is calcined at 400℃ for 10h to obtain a modified single-crystal high-nickel ternary cathode material with surface coating of Li3PO4 and amorphous Li3BO3 composite ionic conductor.

[0063] The SEM image of the modified single-crystal high-nickel ternary cathode material prepared in this embodiment is shown below. Figure 1 As shown, the XRD pattern is as follows Figure 2 As shown.

[0064] Depend on Figure 1 It can be seen that Li3PO4 and Li3BO3 are uniformly coated on the surface; by Figure 2 It can be seen that the co-coating of Li3PO4 and Li3BO3 does not change the layered phase crystal structure of the high-nickel ternary cathode.

[0065] Example 2 This embodiment provides a modified single-crystal high-nickel ternary cathode material, the preparation method of which includes: S1: The ternary cathode material precursor and lithium hydroxide are mixed evenly in a high-speed mixer at a molar ratio of (Ni+Co+Mn):Li of 1:1.04, the doping amount of molybdenum oxide is 2000ppm, and the doping amount of barium hydroxide is 5000ppm. The mixture is then loaded into a sagger and sintered in a high-temperature atmosphere box furnace.

[0066] The sintering process included four stages: a first stage, a second stage, a third stage, and a fourth stage. The sintering atmosphere was oxygen, and the heating rate during the sintering process was 2℃ / min. Specifically, the temperature of the first stage sintering was 450℃ for 4 hours; the temperature of the second stage sintering was 700℃ for 6 hours; the temperature of the third stage sintering was 880℃ for 5 hours; and the temperature of the fourth stage sintering was 700℃ for 5 hours. After sintering, the material was allowed to cool naturally to room temperature to obtain the sintered product. The sintered product was then subjected to jaw crusher, roller mill, airflow milling, and sieving to obtain a cubic ternary cathode material with a (104) crystal plane as the dominant morphology.

[0067] S2: The above-mentioned single-crystal ternary cathode material is mixed with Li3PO4 with a coating amount of 2000ppm and Li3BO3 with a coating amount of 10000ppm. The mixture is mechanically mixed for 1 hour. The mechanically mixed mixture is calcined at 300℃ for 12 hours to obtain a modified single-crystal high-nickel ternary cathode material with surface coating of Li3PO4 and amorphous Li3BO3 composite ionic conductor.

[0068] Example 3 This embodiment provides a modified single-crystal high-nickel ternary cathode material, the preparation method of which includes: S1: The ternary cathode material precursor and lithium hydroxide are mixed evenly in a high-speed mixer at a molar ratio of (Ni+Co+Mn):Li of 1:1.08, the doping amount of molybdenum oxide is 6000ppm, and the doping amount of barium hydroxide is 1000ppm. The mixture is then loaded into a sagger and sintered in a high-temperature atmosphere box furnace.

[0069] The sintering process included four stages: a first stage, a second stage, a third stage, and a fourth stage. The sintering atmosphere was oxygen, and the heating rate during the sintering process was 4℃ / min. Specifically, the temperature of the first stage sintering was 560℃ for 2 hours; the temperature of the second stage sintering was 800℃ for 3 hours; the temperature of the third stage sintering was 1000℃ for 1 hour; and the temperature of the fourth stage sintering was 800℃ for 2 hours. After sintering, the material was allowed to cool naturally to room temperature to obtain the sintered product. The sintered product was then subjected to jaw crusher, roller mill, airflow milling, and sieving to obtain a cubic ternary cathode material with a (104) crystal plane as the dominant morphology.

[0070] S2: The above-mentioned single-crystal ternary cathode material is mixed with Li3PO4 with a coating amount of 10000ppm and Li3BO3 with a coating amount of 2000ppm. The mixture is mechanically mixed for 2 hours. The mechanically mixed mixture is calcined at 500℃ for 8 hours to obtain a modified single-crystal high-nickel ternary cathode material with surface coating of Li3PO4 and amorphous Li3BO3 composite ionic conductor.

[0071] Comparative Example 1 The difference between this comparative example and Example 1 is that in S1, the ternary cathode material precursor and lithium hydroxide are mixed evenly in a high-speed mixer at a molar ratio of (Ni+Co+Mn):Li of 1:1.06 and the molybdenum oxide doping amount is 5000ppm. The mixture is then loaded into a sagger and sintered in a high-temperature atmosphere box furnace.

[0072] That is, the only doping element is Mo, and there is no Ba.

[0073] Comparative Example 2 The difference between this comparative example and Example 1 is that in S1, the ternary cathode material precursor and lithium hydroxide are mixed evenly in a high-speed mixer at a molar ratio of (Ni+Co+Mn):Li of 1:1.06 and the doping amount of barium hydroxide is 5000ppm. The mixture is then placed into a sagger and sintered in a high-temperature atmosphere box furnace.

[0074] That is, the only doping element is Ba, and there is no Mo.

[0075] Comparative Example 3 The difference between this comparative example and Example 1 is that in S1, the molybdenum oxide doping amount is 10,000 ppm.

[0076] That is, the only doping element is Mo, and the doping level of Mo is too high.

[0077] Comparative Example 4 The difference between this comparative example and Example 1 is that in S1, the second and third sintering stages are combined and uniformly carried out at 780°C for 7 hours.

[0078] Comparative Example 5 The difference between this comparative example and Example 1 is that in S1, the second and third sintering stages are combined and uniformly carried out at 950°C for 7 hours.

[0079] Comparative Example 6 The difference between this comparative example and Example 1 is that in S1, the sintering temperature of the second stage is 650°C.

[0080] Comparative Example 7 The difference between this comparative example and Example 1 is that in S1, the sintering temperature of the third stage is 850°C.

[0081] Comparative Example 8 The difference between this comparative example and Example 1 is that in S1, there is no fourth sintering process.

[0082] Comparative Example 9 The difference between this comparative example and Example 1 is that step S2 was not performed.

[0083] Comparative Example 10 The difference between this comparative example and Example 1 is that in S2, the above-mentioned single-crystal ternary cathode material is mixed with Li3PO4 with a coating amount of 7000ppm for 2 hours and then calcined at 500°C for 8 hours.

[0084] That is, the coating material is only Li3PO4.

[0085] Comparative Example 11 The difference between this comparative example and Example 1 is that in S2, the above-mentioned single-crystal ternary cathode material is mixed with Li3BO3 with a coating amount of 7000ppm for 2 hours and then calcined at 500°C for 8 hours.

[0086] That is, the coating material is only Li3BO3.

[0087] Test case The final ternary cathode material products prepared in Examples 1-3 and Comparative Examples 1-11 were assembled into batteries in the following manner and their electrochemical performance was tested.

[0088] The assembly method is as follows: The obtained positive electrode material is mixed with sulfide electrolyte and conductive carbon in a mass ratio of 70:27:3, and ground for 20 minutes until homogeneous to obtain a composite positive electrode. An appropriate amount of sulfide solid electrolyte is placed into the inner liner of the mold battery, pressurized to 300 MPa, and held for 1 minute to obtain the electrolyte layer. The composite positive electrode is then evenly spread on one side of the electrolyte layer, with a positive electrode loading of 20 mg / cm³. 3 The pressure was increased to 300 MPa and held for 1 minute to obtain the positive electrode active material layer. Indium and lithium metal sheets were placed on the other side of the electrolyte layer, and the pressure was increased to 120 MPa and held for 1 minute to obtain the negative electrode layer. The sealed mold battery liner was then placed in a fixture with a clamping pressure of 80 MPa to prepare a sulfide solid-state battery.

[0089] Test conditions included: voltage range of 1.9V to 3.7V, battery charge / discharge rates of 0.1C, 0.2C, 0.33C, 0.5C, and 1C, and room temperature of 25℃.

[0090] The test results are shown in Table 1.

[0091] Table 1 Test Results

[0092] As can be seen from Table 1, the modified single-crystal high-nickel ternary cathode material prepared by the method provided in this invention is more conducive to obtaining sulfide all-solid-state batteries with better electrochemical performance.

[0093] In summary, the method provided by this invention enables the modified single-crystal high-nickel ternary cathode material to have more active crystal faces (104), which is beneficial to improving ion transport efficiency. The coated Li3PO4 and amorphous Li3BO3 composite ion conductor can serve as a buffer and transition layer, effectively isolating the direct contact between the surface of the single crystal particles and the sulfide electrolyte, suppressing the interfacial side reactions between the cathode and the sulfide electrolyte, which can not only improve the structural stability of the cathode, but also improve the ionic conductivity and improve the electrochemical performance of the sulfide all-solid-state battery.

[0094] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A method for preparing a modified single-crystal high-nickel ternary cathode material, characterized in that, Includes the following steps: The ternary cathode material precursor, lithium source, molybdenum source and barium source were mixed and sintered to obtain a single crystal ternary cathode material with (104) crystal plane as the main component and cubic structure. The single-crystal ternary cathode material was mixed with Li3PO4 and Li3BO3 and then calcined to obtain a modified single-crystal high-nickel ternary cathode material with surface-coated Li3PO4 and amorphous Li3BO3 composite ion conductor. The ratio of the total molar amount of Ni, Co, and Mn in the ternary cathode material precursor to the molar amount of Li in the lithium source is 1:(1.04~1.08); the doping amount of Mo in the molybdenum source is 2000ppm~10000ppm, and the doping amount of Ba in the barium source is 1000ppm~5000ppm. The molecular formula of the ternary cathode material precursor is Ni. x Co y Mn z (OH)₂, of which 0.8 <x<0.96,0<y<0.1,0<z<0.1,x+y+z=1; Sintering includes first-stage sintering, second-stage sintering, third-stage sintering, and fourth-stage sintering; The sintering process is as follows: the first sintering temperature is 450℃~560℃ and the time is 2h~4h; the second sintering temperature is 700℃~800℃ and the time is 3h~6h; the third sintering temperature is 880℃~1000℃ and the time is 1h~5h; and the fourth sintering temperature is 700℃~800℃ and the time is 2h~5h.

2. The preparation method according to claim 1, characterized in that, The lithium source includes lithium hydroxide; And / or, the molybdenum source includes molybdenum oxide; And / or, the barium source includes at least one of barium hydroxide, barium chloride, barium nitrate, and barium carbonate.

3. The preparation method according to claim 1, characterized in that, The entire sintering process is carried out in an oxygen atmosphere.

4. The preparation method according to claim 1, characterized in that, The mass of Li3PO4 and Li3BO3 coated on the surface of the single-crystal ternary cathode material is independently 2000ppm~10000ppm.

5. The preparation method according to claim 1, characterized in that, The calcination temperature is 300℃~500℃, and the calcination time is 8h~12h.

6. A modified single-crystal high-nickel ternary cathode material, characterized in that, It is prepared by the preparation method according to any one of claims 1 to 5.

7. A positive electrode sheet, characterized in that, The active material of the positive electrode is the single-crystal high-nickel ternary positive electrode material as described in claim 6.

8. An all-solid-state battery, characterized in that, The all-solid-state battery contains the positive electrode sheet as described in claim 7.

Citation Information

Patent Citations

  • Monocrystal nickel-cobalt-manganese ternary material as well as preparation method and application thereof

    CN118600555A